Comparison of the image system of «Diary» of Alexander Dovzhenko (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
This article examines the comparative constructions in the language of the «Diary» of Alexander Dovzhenko. Stylistic properties and aesthetic role comparisons are analyzed in the text, their place and importance in the individual author's picture of the world.
Keywords: a comparison; comparative constructions; pragmatic function; linguistic personality; linguistic picture of the world